Preoperative Electrophysiology in Patients With Ulnar Nerve Entrapment at the Elbow-Prediction of Surgical Outcome and Influence of Age, Sex and Diabetes - Anker, Ilka; Nyman, Erika; Zimmerman, Malin; Svensson, Ann-Marie; Andersson, Gert S.; Dahlin, Lars B. (Frontiers in Clinical Diabetes and Healthcare, 2022)
The impact of preoperative electrophysiology on outcome of surgical treatment in ulnar nerve entrapment at the elbow (UNE) is not clarified. Our aim was to evaluate influence of preoperative electrophysiologic grading on outcome and analyse how age, sex, and in particular diabetes affect such grading. Electrophysiologic protocols for 406 UNE cases, surgically treated at two hand surgery units reporting to the Swedish National Quality Register for Hand Surgery (HAKIR; 2010-2016), were retrospectively assessed, and graded as normal, reduced conduction velocity, conduction block or axonal degeneration. Outcome of surgery after primary and revision surgery was evaluated using QuickDASH and a doctor reported outcome measure (DROM) grading. No differences in QuickDASH or DROM were found between the four groups with different electrophysiologic grading preoperatively, or at three and 12 months. When dichotomizing the electrophysiologic grading into normal and pathologic electrophysiology, cases with normal electrophysiology had worse QuickDASH than cases with pathologic electrophysiology preoperatively (p=0.046). Presence of a conduction block or axonal degeneration indicated a worse outcome by DROM grading (p=0.011). Primary surgeries had electrophysiologic more pronounced nerve pathology compared to revision surgeries (p=0.017). Cases of older age, men, and those with diabetes had more severe electrophysiologic nerve affection (p<0.0001). In the linear regression analysis, increasing age (unstandardized B=0.03, 95% CI 0.02-0.04; p<0.0001) and presence of diabetes (unstandardized B=0.60, 95% CI 0.25-0.95; p=0.001) were associated with a higher risk of a worse electrophysiologic classification. Female sex was associated with a better electrophysiologic grading (unstandardized B=-0.51, 95% CI -0.75- -0.27; p<0.0001). We conclude that older age, male sex, and concomitant diabetes are associated with more severe preoperative electrophysiologic nerve affection. Preoperative electrophysiologic grade of ulnar nerve affection may influence surgical outcome.